EDUCATING CHILDREN WITH HEART AND SELF-QUALITY: IMPLICATIONS OF KI HADJAR DEWANTARA'S THINKING ON PRIMARY SCHOOL CHARACTER EDUCATION - Yusuf Siswantara; Ace Suryadi; Mupid Hidayat; Ganjar Muhammad Ganeswara; Asnita Sirait (Universitas Majalengka, 2023)
The problem of bad behavior of the younger generation in the form of juvenile delinquency is a major concern in character education in elementary schools. Using qualitative methods, this study aims to raise character education in the educational paradigm of Ki Hadjar Dewantara as a fundamental solution to the problem of juvenile delinquency. The results showed that both the inner interiority in Neng, Ning, Nung, and Nang, the person (will and heart) who is